Comparative Evaluation of Survival Against Fracture in Premolars Treated Endodontically for Cervical Lesions and Restored with Resin and Crowns - Punita Singh; Rameet Sandhu; Pinky Singh; Sahana Karthik; Shobha Bharti; Manish Bhargava (Journal of Pharmacy and Bioallied Sciences)
Background: For endodontic treatment, coronal restoration is crucial in preventing coronal leakage and protecting against fractures in the remaining tooth structure. Aim: To evaluate the effect of the restorations in endodontically treated teeth on survival against fracture in premolars having cervical lesions to identify the prognostic factors depicting the fracture. Methods: Endodontically treated premolars had exposed cervical lesions, and crowns or resin composites were assessed. In the included premolars, the fracture presence was noted along with the prognostic factors associated. The data recorded were analyzed using applicable statistical tests and considering P < 0.05 as the significance level. Results: There was no statistically significant difference in the rates of survival against breakage among teeth replaced with resin composites or crowns, and a decrease in crestal bone in the middle third of the root for fracture was identified as the most important predictor (P < 0.05). Conclusion: In endodontically treated premolar and exposed cervical lesions, a high survival against fracture rate was associated with resin composite restoration compared to the crowns and premolars with crestal bone loss till the middle-third of the root have a high risk of fracture.